From Media to Mediums of Expression. Visual Art Communication and Meaning from Fine Arts to Advertising - Cătălin Soreanu (Anastasis: Research in Medieval Culture and Art, 2020)
In nowadays' explosion of technologies and mediums of communication, there is a recurrence of the pattern of dissemination of the message and of its formative mechanics of meaning, manifested especially in the field of contemporary visual arts and advertising. A comparative analysis of these visual structures of communication could reveal the nature of the interference between the advertising message's subject and theme, and the peculiarities of the meaning specific to the artistic mediums appropriated by the contemporary advertising - namely, the mediums of expression. Targeting the unconventional forms of advertising, as well as the constantly changing relationship of advertising with the technological environments, we will analyze the relationship between the specific expression of the traditional fine arts (graphics, painting, engraving), the contemporary visual arts (such as graphic design, photography, video, or performance), and the characteristics of the message and its meaning in advertising (as expressed in printing, television, or internet). We want to emphasize the importance of these particularities of the visual arts mediums in crafting the communication message, as each of these mediums of expression imposes its expressive mark to the advertising process, decisively influencing the creation of meaning.